A Pragmatic of Speech Acts in Pope Francis Speech Entitled Faith and Freedom - Soidah, Nur Lailatus Syahrul Ula Putri; Andayani, Endah Alamsari; Musyarofah, Lailatul (Journal of English Language and Education, 2026)
Analyzing public speeches requires an understanding of how language expresses both explicit and implicit meaning. Few studies have looked at how speech acts in political and religious contexts interact within a single discourse, while many have looked at these two domains independently. The speech transcript was analyzed and divided into five illocutionary categories using a qualitative descriptive method based on Austin and Searle's Speech Act Theory. The findings reveal that Assertive/Representative behaviors predominate, demonstrating Pope Francis's focus on expressing religious beliefs, factual assertions, and moral argumentation. Additionally, he exhibits expressive, commissive, and directive activities, which demonstrate his attempts to foster group responsibility, commit to future actions, and establish emotional ties. There were no declarative acts discovered. Overall, the study comes to the conclusion that Pope Francis skillfully blends social advocacy and moral persuasion through sensible pragmatic decisions, enhancing the influence of his message on current international concerns.